State Succession - Etinski, Rodoljub (International Law From A Central European Perspective, 2022)
State succession has a variety of aspects. Some general rules on State succession exist but these are colored by specific circumstances and there are international customary rules also. All relevant documents define the term “succession” identically as “the replacement of one State by another in the responsibility for the international relations of territory.” Replacement regarding responsibility for the international relations of a territory occurs between a predecessor State and a successor State. Succession has different types or categories such as the cession, decolonization, unification, secession, and dissolution of a State. The rules on succession of States to treaties reconcile freedom of contracting with the general interests of continuity and certainty of treaty relations. One basic principle is the freedom of contracting. In this context it means that new successor States choose the treaties of the predecessor State to which they will enter. The 1978 Convention governs succession by two basic rules (the automatic succession and clean slate rules), and it also governs the case of transfer of a part of territory and the case of unification. The State property, debts, archives, and private rights and the effect of State succession to nationality are fundamental issues.KEYWORDS: succession, conventions, freedom of contracting, property, debts and archives